Joint myocardial T1 and T2 mapping using a combination of saturation recovery and T2-preparation - Akçakaya, Mehmet; Weingärtner, Sebastian (Magnetic resonance in medicine, 2016)
Purpose To develop a heart-rate independent breath-held joint T1-T2 mapping sequence for accurate simultaneous estimation of coregistered myocardial T1 and T2 maps. Methods A novel preparation scheme combining both a saturation pulse and T2-preparation in a single R-R interval is introduced. The time between these two pulses, as well as the duration of the T2-preparation is varied in each heartbeat, acquiring images with different T1 and T2 weightings, and no magnetization dependence on previous images. Inherently coregistered T1 and T2 maps are calculated from these images. Phantom imaging is performed to compare the proposed maps with spin echo references. In vivo imaging is performed in ten subjects, comparing the accuracy and precision of the proposed technique to existing myocardial T1 and T2 mapping sequences of the same duration. Results Phantom experiments show that the proposed technique provides accurate quantification of T1 and T2 values over a wide-range (T1: 260 ms to 1460 ms, T2: 40 ms to 200 ms). In vivo imaging shows that the proposed sequence quantifies T1 and T2 values similar to a saturation-based T1 mapping and a conventional breath-hold T2 mapping sequence, respectively. Conclusion The proposed sequence allows joint estimation of accurate and coregistered quantitative myocardial T1 and T2 maps in a single breath-hold. Magn Reson Med 76:888-896, 2016. © 2015 Wiley Periodicals, Inc.